2020
DOI: 10.5539/ijef.v12n12p122
|View full text |Cite
|
Sign up to set email alerts
|

Financial Management Practices Among Micro Enterprises and their Implications for Loan Repayment: A Case of Solidarity Group Lending of DCB Commercial Bank in Dar es Salaam

Abstract: The aim of this study was to determine the implications of financial management practices among micro enterprises for loan repayment. The study was confined to Solidarity Group Lending (SGL) customers of DCB Commercial Bank Plc (DCB). Specific objectives included: to identify common practices of managing finances among SGL customers; to determine the extent to which the commonly identified financial management practices influence loan repayment; and to find out challenges facing SGL customers during loan repay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recovering loans from a group loan may be different from the employee and company loans recovering process in which factors determining the repayment may be different (Neilands, 2018;Pandey, 2019;Thomas & Thakur, 2019). Several studies conducted in Kenya, Burkina Faso and Tanzania revealed that loan recovery through group repayment is positively determined by peer pressure, rules of the group, and belongingness to the same business, the level of knowing each other, sex, education and others (Angaine & Waari, 2014;Kitomo et al, 2020;Paxton et al, 2000). Therefore, the determinants of loan recovery are collective and not individualistic.…”
Section: Factors Affecting Loan Recovery Proceduresmentioning
confidence: 99%
“…Recovering loans from a group loan may be different from the employee and company loans recovering process in which factors determining the repayment may be different (Neilands, 2018;Pandey, 2019;Thomas & Thakur, 2019). Several studies conducted in Kenya, Burkina Faso and Tanzania revealed that loan recovery through group repayment is positively determined by peer pressure, rules of the group, and belongingness to the same business, the level of knowing each other, sex, education and others (Angaine & Waari, 2014;Kitomo et al, 2020;Paxton et al, 2000). Therefore, the determinants of loan recovery are collective and not individualistic.…”
Section: Factors Affecting Loan Recovery Proceduresmentioning
confidence: 99%
“…Research has shown that microfinance institutions in Tanzania encounter difficulties in recovering loans, which are further complicated by the methods and processes they utilise (Sikira, 2021). These challenges are exacerbated by factors such as business losses, payment delays from debtors, and issues in managing group members to attend loan centres (Kitomo et al, 2020). In Tanzania, loan recovery has been burdensome to some financial institutions to the extent that a notable portion of recovered funds is allocated to loan recovery efforts (Kasoga & Tegambwage, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, monetary illiteracy along with monetary access have been mentioned as a contributor to the slow development of most small enterprises in South Africa (Owusu, Ismail, Osman, Kuan, 2019;Rambe, Mosweunyane, 2017). More often enterprises are poorly managed and financed, leading to the overall rate of failure of SMEs (Kitomo, Likwachala, Swai 2021).…”
Section: Introductionmentioning
confidence: 99%